(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article is discussed the expanding field of digital therapeutics (DTx) and its intersection with mental health care. It outlines how the integration of digital tools into healthcare systems represents a transformative shift in the prevention, management, and treatment of mental health disorders.